KONSENTRASI PACLOBUTRAZOL DAN PERTUMBUHAN TINGGI BIBIT CENGKEH (Syzygium aromaticum (L.) Merryl & Perry) - Runtunuwu, Semuel D.; Mamarimbing, Rinny; Tumewu, Pemmy; Sondakh, Tommy (Universitas Sam Ratulangi, 2011)
ABSTRACT The purpose of this research was to study the effect of the concentration of growth inhibitor Paclobutrazol (Pbz) against the high growth of clove seedlings (Syzygium aromaticum (L.) Merryl & Perry) and get Pbz concentrations that can produce seed cloves in a relatively short (dwarf). The results showed that spraying Paclobutrazol (Pbz) with 25-100 ppm affect height growth of clove seedlings. Pbz the higher concentration applications, the shorter the length of apical segments produced shoots. In other words, the higher the concentration Pbz, the higher the emphasis on high growth of clove seedlings. Pbz emphasis on high growth of clove seedlings varied from the lowest, ie. 3.79% (25 ppm) up to the highest, ie 69.85% (100 ppm). Based on the comparison of height increment of plants sprayed with Paclobutrazol, the dose applications can be used to get the seed cloves that dwarf is a concentration of 50 to 100 ppm. Key Words :Â Paclobutrazol, Gibberellin, Clove, Dwarfism